Comparison of acute kidney injury between ABO‐compatible and ABO‐incompatible living donor liver transplantation: A propensity matching analysis. Issue 12 (December 2016) - Jun, In‐Gu; Lee, Byungdoo; Kim, Seon‐Ok; Shin, Won‐Jung; Bang, Ji‐Youn; Song, Jun‐Gol; Song, Gi‐Won; Lee, Sung‐Gyu; Hwang, Gyu‐Sam
Abstract : The anti‐CD20 monoclonal antibody rituximab has significantly decreased the prevalence of antibody‐mediated rejection of ABO‐incompatible (ABOi) living donor liver transplantation (LDLT). However, little is known about acute kidney injury (AKI) following ABOi LDLT. The aim of this study was to identify the incidence of AKI in ABOi LDLT and compare it with that of ABO‐compatible (ABOc) LDLT. We retrospectively collected and analyzed the data of 1617 patients who underwent liver transplant surgery from November 2008 to December 2014. Risk factors for AKI were investigated using multivariate regression analysis. In 271 ABOi LDLTs, AKI occurred in 184 (67.9%) according to Kidney Disease: Improving Global Outcomes criteria. After propensity score matching, the incidence of AKI was significantly higher after ABOi LDLT than after ABOc LDLT (67.0% versus 48.2%; P  < 0.001). Furthermore, the intensive care unit stay ( P  = 0.01) was significantly prolonged, but there were no significant differences in mortality ( P  = 0.74), graft failure ( P  = 0.32), and postoperative dialysis ( P  = 0.74) between the 2 groups. Hemoglobin level and operation time were independent risk factors for AKI following ABOi LDLT. In conclusion, the incidence of AKI is higher in ABOi LDLT than ABOc LDLT. However, the impact of AKI on postoperative outcomes was not marked in our study. Therefore, ABOi LDLT in selected patients is promising with apparent good graft and survival outcomes. Liver Transplantation 22 1656–1665 2016 AASLD .